2014
DOI: 10.1097/shk.0000000000000209
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Mucus Layer is a Critical Component of the Gut Barrier that is Damaged During Acute Pancreatitis

Abstract: Background Gut barrier failure has been implicated in the progression from single organ injury to multiple organ failure. The unstirred mucus layer is a major component of the physiological gut barrier, its role in acute pancreatitis(AP) is not clearly defined. Study Design Rats underwent biliopancreatic duct ligation-induced AP; two controls were used: biliopancreatic duct ligation with drainage and sham duct ligation. After 4.5 hours, serum and ascitic amylase activity was measured. Mucus was analyzed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 34 publications
1
39
0
3
Order By: Relevance
“…The present study revealed that 90 min of hemorrhagic shock followed by resuscitation decreased the levels of lysozyme and mucin 2, consistent with previous reports in different mouse models of IR [11,13,24]. Consequently, decreased lysozyme and mucin 2 levels in the intestinal mucosa may contribute to increased bacterial translocation after HSR [25]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study revealed that 90 min of hemorrhagic shock followed by resuscitation decreased the levels of lysozyme and mucin 2, consistent with previous reports in different mouse models of IR [11,13,24]. Consequently, decreased lysozyme and mucin 2 levels in the intestinal mucosa may contribute to increased bacterial translocation after HSR [25]. …”
Section: Discussionsupporting
confidence: 92%
“…However, it remains to be determined why n -6 PUFAs, but not lysozyme, enhanced the expression of mucin 2, but not lysozyme, IL-4, or IL-10. In addition, n -6 PUFAs also ameliorated bacterial translocation after HSR in MLN, possibly through increased mucin 2 expression [25]. It should be noted, however, that exogenous addition of n -3 PUFAs or n -6 PUFAs failed to revert the low expression of the antibacterial lectin RegIIIγ.…”
Section: Discussionmentioning
confidence: 99%
“…The mucosal barrier is well recognized for its ability to prevent undigested food or bacteria from passing across the epithelial cells into the mucosal space of the intestinal villi (16,17). In the context of the current discussion, the intestinal mucosal barrier serves to compartmentalize the digestive enzymes inside the lumen of the intestine.…”
Section: Mucosal Barriermentioning
confidence: 99%
“…S13); two inducible enzymes that mediate PGE 2 synthesis (4). Acute pancreatitis (AP) is a sterile initiator of systemic inflammation that results in multiple organ dysfunction where gut barrier injury is central to the pathogenesis (30). Given that IL-22 was protective in an animal model of AP (31), we measured IL-22 levels in patients with AP.…”
mentioning
confidence: 99%